Succession of Microbial Communities in Waste Soils of an Iron Mine in Eastern China - Qin Zhang; Pengfei Wei; Joseph Frazer Banda; Linqiang Ma; Weiao Mao; Hongyi Li; Chunbo Hao; Hailiang Dong (Microorganisms, 2021)
The reclamation of mine dump is largely centered on the role played by microorganisms. However, the succession of microbial community structure and function in ecological restoration of the mine soils is still poorly understood. In this study, soil samples with different stacking time were collected from the dump of an iron mine in China and the physicochemical characteristics and microbial communities of these samples were comparatively investigated. The results showed that the fresh bare samples had the lowest pH, highest ion concentration, and were the most deficient in nutrients while the acidity and ion concentration of old bare samples decreased significantly, and the nutritional conditions improved remarkably. Vegetated samples had the weakest acidity, lowest ion concentration, and the highest nutrient concentration. In the fresh mine soils, the iron/sulfur-oxidizers such as Acidiferrobacter and Sulfobacillus were dominant, resulting in the strongest acidity. Bacteria from genera Acidibacter, Metallibacterium, and phyla Cyanobacteria, WPS-2 were abundant in the old bare samples, which contributed to the pH increase and TOC accumulation respectively. Acidobacteriota predominated in the vegetated samples and promoted nutrient enrichment and plant growth significantly. The microbial diversity and evenness of the three types of soils increased gradually, with more complex microbial networks, suggesting that the microbial community became more mature with time and microorganisms co-evolved with the mine soils.